2022
DOI: 10.1371/journal.pntd.0010205
|View full text |Cite
|
Sign up to set email alerts
|

First laboratory confirmation and sequencing of Zaire ebolavirus in Uganda following two independent introductions of cases from the 10th Ebola Outbreak in the Democratic Republic of the Congo, June 2019

Abstract: Uganda established a domestic Viral Hemorrhagic Fever (VHF) testing capacity in 2010 in response to the increasing occurrence of filovirus outbreaks. In July 2018, the neighboring Democratic Republic of Congo (DRC) experienced its 10th Ebola Virus Disease (EVD) outbreak and for the duration of the outbreak, the Ugandan Ministry of Health (MOH) initiated a national EVD preparedness stance. Almost one year later, on 10th June 2019, three family members who had contracted EVD in the DRC crossed into Uganda to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, it is important to note that 2018 had heightened surveillance because of Ebola virus disease (EVD) outbreak in the neighboring Democratic Republic of the Congo (DRC). 22 When comparing individuals who tested positive for RVFV with those who tested negative from the same homesteads, statistically significant relationships were found for most sociodemographic factors (Table 3). Bivariate analysis using a x 2 test found that RVF positivity was associated with age, gender, geographic region of Uganda, being a butcher, and having contacts with livestock (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that 2018 had heightened surveillance because of Ebola virus disease (EVD) outbreak in the neighboring Democratic Republic of the Congo (DRC). 22 When comparing individuals who tested positive for RVFV with those who tested negative from the same homesteads, statistically significant relationships were found for most sociodemographic factors (Table 3). Bivariate analysis using a x 2 test found that RVF positivity was associated with age, gender, geographic region of Uganda, being a butcher, and having contacts with livestock (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…At UVRI, samples were processed for EBOD confirmation using previously reported methods ( 18 , 24 ). Briefly, the MagMax Kit (Applied Biosystems Inc., Vilnius, Lithuania) was used to extract RNA, followed by RT-PCR on ABI’s QuantStudio 5 or 7500 Real-Time PCR System instruments (Applied Biosystems), using the US CDC custom primers and probes that target the NP region for SUDV [EboSudBMG 1(+) 5′-GCC ATG GIT TCA GGT TTG AG-3′, EboSudBMG 1(−) 5′-GGT IAC ATT GGG CAA CAA TTC A, and EboSudBMG Probe 5′FAM-AC GGT GCA CAT TCT CCT TTT CTC GGA-BHQ1] ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, it highlights the need to develop new biomarkers to help diagnose CCHFV. Platelets, AST, ALT, first-step coagulation assays, LDH creatinine, and fibrinogen have all been identified as laboratory indications of CCHFV [68][69][70]. After the acute phase of the infection, which lasts 4-9 days after symptoms appear, active CCHFV infection may be identified by IgM or a substantial rise in IgG titer; however, severe and fatal cases often do not develop a detectable Ab response.…”
Section: Standard Molecular Detectionmentioning
confidence: 99%